2014
DOI: 10.1152/jn.00329.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cortical regulation of dopaminergic neurons: role of the midbrain superior colliculus

Abstract: Dopaminergic (DA) neurons respond to stimuli in a wide range of modalities, although the origin of the afferent sensory signals has only recently begun to emerge. In the case of vision, an important source of short-latency sensory information seems to be the midbrain superior colliculus (SC). However, longer-latency responses have been identified that are less compatible with the primitive perceptual capacities of the colliculus. Rather, they seem more in keeping with the processing capabilities of the cortex.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Our results have demonstrated that the regulation of neural development by netrin‐1/DCC signaling may be mediated, at least in part, through the activation of PLCγ1, which controls key steps in the axonal projection of mDA neurons as well as CC structural formation. In particular, mDA neurons have been implicated in various kinds of neurological disorders such as addiction, parkinsonism, schizophrenia, sleep abnormalities, and ADHD, with some evidence indicating that structural changes in neuronal networks may in part underlie the pathogenesis of these disorders . Although axon guidance events are crucial for the correct development of mDA pathways, their precise role during the pathogenesis of mDA system‐related disorders has not been established.…”
Section: Resultsmentioning
confidence: 99%
“…Our results have demonstrated that the regulation of neural development by netrin‐1/DCC signaling may be mediated, at least in part, through the activation of PLCγ1, which controls key steps in the axonal projection of mDA neurons as well as CC structural formation. In particular, mDA neurons have been implicated in various kinds of neurological disorders such as addiction, parkinsonism, schizophrenia, sleep abnormalities, and ADHD, with some evidence indicating that structural changes in neuronal networks may in part underlie the pathogenesis of these disorders . Although axon guidance events are crucial for the correct development of mDA pathways, their precise role during the pathogenesis of mDA system‐related disorders has not been established.…”
Section: Resultsmentioning
confidence: 99%
“…Watabe-Uchida et al [ 23 ] found that dopaminergic neurons in the ventral tegmental area and substantia nigra pars compacta receive sparse input from the deep layers of cortex (for example their Fig 5 ). Because of the well established role of these midbrain structures in valuation, motivation, and reinforcement learning, these authors suggest that these dopaminergic neurons might “calculate the difference between the expected and actual reward (i.e., reward prediction errors).” While speculative, it is possible that this prediction is calculated cortically and relayed either directly or indirectly [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have also found strong innervation from the lateral pallium to the optic tectum, especially abundant in the deep output layer. Our results suggest that the lateral pallium/cortex may, in addition to direct projections, send information to the SNc through the tectum/ superior colliculus, a pathway that was very recently shown in rats (Bertram et al, 2013).…”
Section: Cortical Modulation Of the Sncmentioning
confidence: 99%